Multiple ligands simultaneous molecular docking and dynamics approach to study the synergetic inhibitory of curcumin analogs on ErbB4 tyrosine phosphorylation - La Ode Aman; Netty Ino Ischak; Teti Sutriyati Tuloli; Arfan Arfan; Aiyi Asnawi (Research in Pharmaceutical Sciences)
Background and purpose: Lapatinib (FMM) and 5-fluorouracil (5-FU) are anticancer drugs employed in a combination approach. FMM inhibits tyrosine phosphorylation of ErbB4 while 5-FU inhibits cell proliferation. This research aimed to investigate the potential of two compounds, namely (1E,4E)-1,5-bis (4-hydroxyphenyl) penta-1,4-dien-3-one (AC01) and (1E,4E)-1,5-bis (3,4-dihydroxy phenyl) penta-1,4-dien-3-one (AC02), both as individual inhibitors and combination partners with FMM, targeting ErbB4 inhibition. AC01 and AC02 were combined with FMM, which targets ErbB4. The combination of 5-FU with FMM served as a reference in this study. Experimental approach: The research utilized computational simulation methods such as single and multiple ligands simultaneously docking and dynamics. Data analysis was performed using AutoDockTools and gmx_MMPBSA. Findings/Results: Single docking results indicated that 5-FU exhibited the lowest binding affinity, while FMM demonstrated the highest. Simultaneous docking of AC01 and AC02 paired with FMM revealed their binding positions overlapping with the FMM-5-FU workspace. The FMM-AC01 and FMM-AC02 complexes exhibited slightly weaker binding affinities compared to FMM-5-FU. In combination with FMM, AC01 and AC02 occupied the ErbB4 activation loop, whereas 5-FU was outside the activation loop. Furthermore, in their interaction with ErbB4, AC02 exhibited slightly stronger binding than AC01, as confirmed by the average binding free energy calculations from molecular dynamics simulations. Conclusion and implications: In conclusion, computational simulations indicated that both AC01 and AC02 have the potential to act as anticancer candidates, demonstrating ErbB4 inhibitory potential both as individual agents and in synergy with FMM.